Pengembangan Game "Days With Suroboyo Bus" Sebagai Media Pengenalan Transportasi Suroboyo Bus - Gede Satria Harinamanata; Issa Arwani; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The plastic waste problem becomes a threat to wildlife in the world. Surabaya City Government launched the Suroboyo Bus program that uses used bottles and plastic cups as a means of payment to tackle the problem of plastic waste for the environment. Public awareness is needed to increase the effectiveness of this program, one of which is through video games. The game "Days with Suroboyo Bus" was developed using the Design Framework, Dynamics, Experience (DDE), a framework developed from the Mechanics, Design, Aesthetics (MDA) framework. Development begins with determining the design of the game, followed by the implementation of the design that will create the dynamics of the game, and creating experiences for the players who play it. Its development calculates playtesting by using the Gameplay Scale and Appeal Scale. Gameplay Scale test results on the game "Days with Suroboyo Bus" showed Affective Experience (75.71428571%), Focus (71.58730159%), and Usability Barrier (75.71428571%) had good values. While the Playability Barrier (70.85714286) has a Slightly Good value. Test scale on the game "Days with Suroboyo Bus" has a pleasant result (74.28571429), good (80), aesthetic (75.71428571), a little evocative (70), interesting (75.71428571), easy to motivate to play (57.14285714), desirable (67.14285714) ) and tend to be happy (64.28571429).